The effect of hybrid learning-based I-book media to improve language literacy in elementary schools - Mohd. Lutfi Alhadi; Adisti Yuliastrin; Rian Vebrianto (Jurnal Penelitian Ilmu Pendidikan, 2023)
Literacy culture in Indonesia is an exciting issue to discuss. Related to this matter, a current study aimed to improve the language literacy skills in elementary school students based on the Hybrid Learning media I-book. Various kinds of exercises based on language literacy are provided in the I-Book. Thus, its use can save money when buying books. In addition, students are enthusiastic about answering the practice questions in the I-Book because of its attractive and colorful appearance. In this case, the I-book is a medium that can be applied in hybrid learning education in language literacy. The research method used in this study was quasi-experimental in the form of a non-equivalent control group design. In this case, the samples were selected using purposive sampling. The two sample classes used were III A (control) and III B (experiment). The results of the effectiveness of the N-Gain pretest and posttest of student learning outcomes in the control class obtained 0.30 in the low category, while the experimental class obtained 0.57 in the medium category. Furthermore, the results of the independent t-test on sig. (2-tailed) obtained 0.047 <0.05, indicating a significant difference between the results of the control class and the experimental class learning process. The research results found that using the I-Book as a hybrid learning educational media in language literacy made it easier for teachers to improve the students' language literacy skills so that teachers and stakeholders can use the I-Book as a practical learning media. Pengaruh media I-book berbasis hybrid learning terhadap peningkatan literasi bahasa Budaya literasi di Indonesia menjadi persoalan yang sangat menarik untuk diperbincangkan. Berhubungan dengan hal ini, penelitian ini dilakukan dengan tujuan untuk meningkat kemampuan literasi bahasa pada peserta didik di sekolah dasar dengan berbasis pada Hybrid Learning media I-book. Berbagai macam latihan berbasis literasi bahasa disediakan di dalam I-Book, sehingga penggunaannya dapat menghemat biaya membeli buku. Selain itu, siswa juga menjadi semangat mengerjakan latihan soal yang terdapat pada I-Book karena tampilannya yang menarik dan berwarna. Dalam hal ini, I-Book adalah media yang digunakan dalam pembelajaran hybrid pada literasi bahasa. Metode penelitian yang digunakan dalam penelitian ini adalah  metode eksperimen semu dalam bentuk nonequivalent control group design, di mana sampel penelitian diambil menggunakan purposive sampling. Dua kelas sampel yang digunakan adalah kelas III A (kontrol) III B (eksperimen). Hasil  efektifitas pretest  N-Gain  dan  posttest  hasil belajar siswa  pada  kelas  kontrol adalah 0.30 dengan kategori rendah, sedangkan kelas eksperimen mendapatkan 0,57 pada kategori sedang. Selain itu, hasil uji-t independent pada sig. (2-tailed) yang didapatkan adalah 0,047<0,05, yang berarti bahwa terdapat perbedaan yang signifikan antara hasil kelas kontrol dan kelas   eksperimen. Berdasarkan hasil penelitian, ditemukan bahwa pembelajaran menggunakan I-Book sebagai media edukasi hybrid learning pada literasi bahasa memudahkan guru dalam pembelajaran sehingga para guru dan stakeholder dapat menggunakan I-Book sebagai pembelajaran yang efektif